How can consultant-led childbirth care at time of delivery be maximised? A modelling study. Issue 7 (8th July 2020) - Allen, Michael; Villeneuve, Emma; Pitt, Martin; Thornton, Steve
Abstract : Objective: The Royal College of Obstetricians and Gynaecologists has advised that consolidation of birth centres, where reasonable, into birth centres of at least 6000 admissions per year should allow constant consultant presence. Currently, only 17% of mothers attend such birth centres. The objective of this work was to examine the feasibility of consolidation of birth centres, from the perspectives of birth centre size and travel times for mothers. Design: Computer-based optimisation. Setting: Hospital-based births. Population or sample: 1.91 million admissions in 2014–2016. Methods: A multiple-objective genetic algorithm. Main outcome measures: Travel time for mothers and size of birth centres. Results: Currently, with 161 birth centres, 17% of women attend a birth centre with at least 6000 admissions per year. We estimate that 95% of women have a travel time of 30 min or less. An example scenario, with 100 birth centres, could provide 75% of care in birth centres with at least 6000 admissions per year, with 95% of women travelling 35 min or less to their closest birth centre. Planning at local level leads to reduced ability to meet admission and travel time targets. Conclusions: While it seems unrealistic to have all births in birth centres with at least 6000 admissions per year, it appears realistic to increase the percentage of mothers attending this type of birth centre from 17% to about 75% while maintaining reasonable travel times. Planning at a local level leads to suboptimal solutions.